Water splitting performance of metal and non-metal-doped transition metal oxide electrocatalysts - Al-Naggar, Ahmed H.; Shinde, Nanasaheb M.; Kim, Jeom-Soo; Mane, Rajaram S. (Coordination chemistry reviews, 2023)
The effects of heteroatom-doping on transition metal oxide-based electrocatalysts toward overall water splitting performance. [Display omitted] •The basics of electrochemistry for water splitting process are elucidated.•Doping processes for preparing heteroatom (metal and non-metal)-doped TMOs are briefed.•Concepts like doping, elemental incorporation and alloying are addressed.•Future scope, current challenges and outlook of heteroatom (metal and non-metal)-doped TMOs in electrocatalysts are highlighted.•Based on information provided, in this review, researchers can revolutionize overall water splitting electrocatalyst for commercial benefits. Transition metal oxide electrocatalysts have received significant research interest toward the advancement of environmentally acceptable electrochemical applications and systems, which are considered to be promising technologies due to their unique physicochemical properties like low cost, robust durability, structural flexibility, and tunable activity. However, transition metal oxide-based electrocatalysts suffer from poor electrocatalytic activity as well as a limited number of active sites, which result in the obstruction of their applications over the world. To overcome these challenges, heteroatom-doping into transition metal oxide electrocatalysts has been a crucial and rapid way to improve the conductivity of the catalytic centers and optimize the adsorption of the reactants and intermediates during the catalytic process, and hence, their electrocatalytic activity, which has become widespread in nanomaterials, is offering the possibility to select the catalytic properties with attractive traits for a specific application to some extent. We have critically and systematically discussed the recent progress on doping strategy involves non-noble metallic elements, such as Fe, Co, Mn, Ni, Ru, Mo, W, Cu, etc., and non–metallic elements, such as S, N, P, B, Se, F, C, etc., in transition metal oxide-based electrocatalysts for water splitting performance to gain a better understanding of the relationship between effect of heteroatoms doping engineering techniques and TMOs catalytic properties. Most importantly, doping, elemental incorporation and alloying perform a significant role with heteroatoms for improving the catalytic activity on; modifying the electronic configuration of the catalysts, increasing the number of active sites, enhancing the electrical conductivity, and inducing synergistic effect of the transition metal oxide-based electrocatalysts during overall water splitting process. We here also have briefly described the techniques used for preparing metal and non-metal-doped transition metal oxide-based electrocatalysts for overall water splitting process. In nutshell, this review is expected to provide a deeper insight on the effect of the metal and non-metal-doping in transition metal oxide-based electrocatalysts for the rational design of high-performance catalysts in the future. We also have provided the current challenges and future perspectives of heteroatom-doped transition metal oxide-based electrocatalysts for the development of high-performance water splitting processes.